2012
DOI: 10.1039/c2an15798e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of red blood cells agglutination in antibody-treated paper

Abstract: Recent reports on using bio-active paper and bio-active thread to determine human blood type have shown a tremendous potential of using these low-cost materials to build bio-sensors for blood diagnosis. In this work we focus on understanding the mechanisms of red blood cell agglutination in the antibody-loaded paper. We semi-quantitatively evaluate the percentage of antibody molecules that are adsorbed on cellulose fibres and can potentially immobilize red blood cells on the fibre surface, and the percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 29 publications
1
65
0
3
Order By: Relevance
“…The conventional sandwich ELISA technique involves plate preparation using primary antibody. Researchers have demonstrated that antibodies can be physisorbed or ink jet printed on paper, and can be used for further applications [1][2][3]46]. In this study, the paper was used as an alternative surface to perform the sandwich ELISA test to detect viruses.…”
Section: Discussionmentioning
confidence: 97%
“…The conventional sandwich ELISA technique involves plate preparation using primary antibody. Researchers have demonstrated that antibodies can be physisorbed or ink jet printed on paper, and can be used for further applications [1][2][3]46]. In this study, the paper was used as an alternative surface to perform the sandwich ELISA test to detect viruses.…”
Section: Discussionmentioning
confidence: 97%
“…A new generation of low cost and easy to use paper diagnostics has recently been developed for blood typing [8][9][10][11][12][13]. The concept relies on specific antibody-antigen interactions to selectively agglutinate red blood cells (RBC) on paper, to separate the agglutinated RBC (positive) from the non-agglutinated RBC (negative), to directly communicate results; the paper test can also be retained as a document.…”
Section: Introductionmentioning
confidence: 99%
“…The primary structure can only be affected by chemical reactions (Kubo, 1995). In blood-grouping paper diagnostics, antibodies are released from the substrate to trigger the agglutination within antigen-positive red blood cells (RBCs) (Jarujamrus et al, 2012). However, the partial release of antibodies was reported after long aging periods, leading to sensor invalidity (Sajid et al, 2015).…”
Section: Introductionmentioning
confidence: 99%